Tourism-related Crime: Towards a Sociology of Crime and Tourism - Cohen, Erik (1997)
The purpose of this article is to: (1) categorize tourist-related crime, (2) relate these types of crimes to current criminological theories, and (3) place tourist-related crime into the broader social context. Through this analysis, a conceptual framework was developed to specify the factors determining the probabilities and the potential rates of success of certain kinds of offenders against different types of tourists in various situations